Room-Temperature and Transition-Metal-Free Mizoroki Heck-type Reaction. Synthesis of E-Stilbenes by Photoinduced C-H Functionalization - Guastavino, Javier Fernando (2014)
We report a conceptually different approach toward E-stilbene syntheses by photoinduced direct C-H arylation of alkenes at rt without the addition of transition metals, with a broad range of aryl halides, including ArI, ArBr, and even ArCl. This is the first time that this reaction has been produced without extra solvent but with 18-crown-6 ether and t-BuOK in only 15 min of reaction.